Simulation of Self-Healing in Samawa City Distribution System - Mithaq Kadham; Thamir Abdul-Wahhab (Engineering and Technology Journal, 2020)
Self-healing is the ability of a distribution system to automatically restore power after permanent faults. This paper investigates the impact of outages in the distribution network elements following the occurrence of a fault. The work aims to restore maximum available power to consumers in the affected areas, after the isolation of faulted parts, by optimal procedure of switching operations. In this work, CYMDIST software was used for the simulation and analyses of a distribution network in Samawa City. MATLAB 2017b/Simulink was used to implement self-healing, through the simulation of smart protection system that is controlled remotely by a central control unit. The results of implementing the proposed self-healing system on Samawa a New 11 kV network show a maximum power restoration with a minimum number of switching operations that have been achieved after fault isolation without violating constraints.